Exploring risky youth experiences : Popular theatre as a participatory, performative research method - Conrad, Diane (International Journal of Qualitative MethodsInternational Journal of Qualitative Methods, 2004)
This article discusses a Popular Theatre project with a group of high school drama students in a rural Alberta community. As a research method, Popular Theatre draws on traditions in participatory research and performance ethnography. In our project, entitled “Life in the Sticks,” based on students’ initial claims that their issues were determined by their rural environment, Popular Theatre was a way to collectively draw out, represent and question their experiences through theatrical means. Our process helped students re-examine their beliefs and helped me reframe the notion “at-risk” to include the perceptions of youth. Popular Theatre is shown to be an effective pedagogical tool and research method in the new insights and critical understandings it yielded.
Keywords: arts; méthodologie; participation; pédagogie